Efektivitas Psikoedukasi Problem Focused Coping: dalam Menurunkan Caregivers Emotional Burden Lansia - Nathania Maheswari Nugrastuti; Titik Mut’iah; Haniek Farida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The elderly need support from companions or caregivers, both from family and volunteers. Elderly care requires a lot of time and effort, especially when the elderly experience conditions such as dementia, chronic diseases, or physical disabilities. The majority of elderly nurses in Indonesia come from family environments because the culture in Indonesia emphasizes kinship and attachment between families. A caregiver is an individual who has a personal relationship such as family, friends, or relatives who are willing to volunteer to help an individual with a chronic illness or disability. Family Caregivers often experience the emotional burden of stress, physical and mental exhaustion, as well as mental health issues such as depression and anxiety, as the average caregiver spends about 8-13 hours per day caring for them. This study aims to determine the effectiveness of psychoeducational problem focused coping in reducing the emotional burden of elderly caregivers. This research method uses an experimental research method with a nonequivalent design. The hypothesis of this study is whether psychoeducation problem-focused coping effectively reduces the emotional burden of caregivers of the elderly in Kulon Progo with the types of a control group and an experimental group. The results of this study showed that v by as much as 0.000<0.05, aimed at reducing emotional burden in the experimental group compared to the control group that did not receive treatment. Psychoeducation of problem focused coping can be used as one of the methods that can be used to reduce the emotional burden on caregivers